Extraction And Quantitative Determination Of Ascorbic Acid From Banana Peel Musa Acuminata ‘Kepok’ - Khairul Anwar, Mohamad Said; Zainad, Radzi; Ibrahim, Yakub; Mohamed Afizal, Mohamed Amin (International Islamic University Malaysia, 2016)
This paper discusses the extraction of an antioxidant compound, which is ascorbic acid or vitamin C, from a banana peel using an ultrasound-assisted extraction (UAE) method. The type of banana used was Musa acuminata also known as “PisangKepok” in Malaysia. The investigation includes the effect of solvent/solid ratio (4.5, 5 g and 10 ml/g), sonication time (15, 30 and 45 mins) and temperature variation (30 , 45 and 60oC ) on the extraction of ascorbic acid compounds from the banana peel to determine the best or optimum condition of the operation. Out of all extract samples analyzed by redox titration method using iodine solution, it was found that the highest yield was 0.04939 ± 0.00080 mg that resulted from an extraction at 30oC for 15 mins with 5 ml/g solvent-to-solute ratio.